2018
DOI: 10.1016/j.ram.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Detección de Chlamydia abortus en pérdidas reproductivas de bovinos en la provincia de La Pampa, Argentina

Abstract: Reproductive losses linked to an infectious etiology in bovine cattle are a major economic concern worldwide. In Argentina, more than 50% of abortion cases have unknown causes. Species belonging to Chlamydiaceae family are frequent etiologic agents of abortion around the world; however, there is yet no information on their prevalence in Argentina. The objective of this work was to identify Chlamydia spp., and particularly C. abortus in reproductive losses from bovine cattle in La Pampa, Argentina. Real time PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
4
0
3
Order By: Relevance
“…Recently Rojas et al . () detected Chlamydiaceae DNA in 12 samples of 251 bovine aborted fetuses (4.78%) and C. abortus was detected in five of the studied cases (1.99%). The mentioned study confirmed the presence of C. abortus in La Pampa Province, not far from Mendoza Province, the location of the present case.…”
Section: Discussionmentioning
confidence: 88%
“…Recently Rojas et al . () detected Chlamydiaceae DNA in 12 samples of 251 bovine aborted fetuses (4.78%) and C. abortus was detected in five of the studied cases (1.99%). The mentioned study confirmed the presence of C. abortus in La Pampa Province, not far from Mendoza Province, the location of the present case.…”
Section: Discussionmentioning
confidence: 88%
“…apresentem baixa especificidade ao hospedeiro, os búfalos e bovinos possuem características semelhantes, fazendo com que o agente também possa estar relacionado a distúrbios reprodutivos na espécie bubalina [15]. m bovinos baixas prevalências foram relatadas na Costa Rica com 0,10% [33], no Iraque com 0,82% [18], no Brasil com 1,42% [36] e na Argentina com 4,78% [31] em comparação às prevalências encontradas em bubalinos que foram de 11,67% [2] e 78,43% [25] no Egito e 57% [15] na Itália. Mesmo não sendo identificados os fatores de risco, o manejo semi-intensivo a extensivo que ocorre em propriedades com búfalos poderia explicar a frequência de anticorpos, já que o contato entre animais criados a pasto pode favorecer a infecção por via oral [26,39].…”
Section: Resultsunclassified
“…This study highlights the need to advance in the knowledge of C. abortus and its involvement in reproductive problems. Considering the increase in the number of reports about the participation of this bacterium in bovine abortion syndrome, it is worth noting that 50% of the cases ended without a definitive diagnosis ( Kauffold et al., 2007 ; Rojas et al., 2018 ). Additionally, this is a serious public health problem due to the participation of C. abortus in women abortion ( Essig and Longbottom, 2015 ; Longbottom and Coulter, 2003 ; Pospischil et al., 2002 ).…”
Section: Discussionmentioning
confidence: 99%